Answer:
![5\sqrt[3]{7}*y^3*x^{(5)/(3)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lvqnlhfwb9ob7tjp17nct689wn2lyvcouo.png)
Explanation:
We are asked to simplify the radical expression:
.
Using exponent rule for radical
we can rewrite our expression as:
![\sqrt[3]{875x^5y^9}=\sqrt[3]{875}*\sqrt[3]{x^5}*\sqrt[3]{y^9}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jtmkrha4bv4gwpzstqsyrnq9xwgx94dp5y.png)
![\sqrt[3]{875}=\sqrt[3]{125*7}=5\sqrt[3]{7}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/orzqqv5ecq8q5q8adk9armc3srl6y78h3e.png)
Using exponent rules for radical
we will get,
![\sqrt[3]{x^5}=(x^5)^{(1)/(3)}=x^{(5)/(3)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/svbyy4ar2k88dmg7abikx2ymop1ydb131x.png)
Using exponent rules for radical
we will get,
![\sqrt[3]{y^9}=(y^9)^3=y^{(9)/(3)}=y^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z93qk5tbihgvjnm01j91h5t0x83yynay6z.png)
Upon substituting these values in our expression we will get,
![\sqrt[3]{x^5}*\sqrt[3]{y^9}=5\sqrt[3]{7}*x^{(5)/(3)}*y^3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mf545m2zetqjzaoh66caavm1fsshebnxok.png)
Therefore, our radical expression simplifies to
.